Respuesta :
Answer:
Product of two expression is [tex](6x-y)(2x-y)=12x^2-8xy+y^2[/tex]
Step-by-step explanation:
Given : Expression - [tex]6x- y[/tex] and [tex]2x-y[/tex]
To find : The product of given expression
Solution : To find the product we apply distributive law
[tex]a(b+c)=ab+ac[/tex]
We write in the form of product and multiply term by term
[tex](6x-y)(2x-y)[/tex]
[tex]=(6x)(2x-y)-y(2x-y)[/tex]
Apply distributive law,
[tex]=(6x)(2x)-(6x)(y)-y(2x)+(y)(y)[/tex]
[tex]=12x^2-6xy-2xy+y^2[/tex]
[tex]=12x^2-8xy+y^2[/tex]
Therefore, Product of two expression is [tex](6x-y)(2x-y)=12x^2-8xy+y^2[/tex]